1986
DOI: 10.1038/bjc.1986.254
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunotherapy of malignancy using antibody targeted radionuclides

Abstract: Summary Antibodies directed against tumour associated antigens provide a means for delivering preferentially cytotoxic radionuclides to the cells of primary and secondary tumours. The factors that influence the effectiveness of the radiation in the tumour compared with its effect on the radiosensitive normal tissues include the specificity of the antibody, the distribution of targeted energy within the tumour and the host's response to the injected foreign antibody. Recently some encouraging results from clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…ß x C • AC (2) where C is the cpm emitted by the organ or tumor in the ROI and AC is the correction value to correct the attenuation in the body.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ß x C • AC (2) where C is the cpm emitted by the organ or tumor in the ROI and AC is the correction value to correct the attenuation in the body.…”
Section: Methodsmentioning
confidence: 99%
“…4. Attenuation correction was performed with formula (2). In this calculation, we used 1.56 as the correction value AC in formula (2), which was computed on the basis of Appendix 1.…”
Section: Bone Marrowmentioning
confidence: 99%
“…In contrast, for beta radiation 400 times as many impacts are required. It has been estimated that when sparsely ionizing (low LET) gamma and/or beta radiation is used, 200 double-strand breaks in the DNA of the cell are required to sterilize 99% of a tumor cell population (37). With the densely ionizing (high LET) alpha particles only a few DNA-breaks are needed and one traversal of such a heavy particle through the nucleus of a cell may be lethal.…”
Section: Radiobiological Considerationsmentioning
confidence: 99%
“…In general these are ill-defined high molecular weight antigens with a substantial proportion of carbohydrate and the Mabs involved have limited effect. The amount of isotope used in targeting needs therefore to be considerable (Cobb & Humm, 1986;Baldwin & Byers, 1986) and it has been suggested that the dose required to eliminate the tumour entirely is likely to be unacceptably high (Vaughan et al, 1986). There is still therefore a requirement for more specific Mabs with a high tumour/normal cell ratio.…”
mentioning
confidence: 99%
“…In a large proportion of patients an immune response to the foreign mouse immunoglobulin is generated by the patient and therefore a second or third application of antibody is quickly removed from the system before it can have any beneficial effect (reviewed by Cobb & Humm, 1986).…”
mentioning
confidence: 99%